ENHANCES JURIDICAL OF CIVIL CASES ON LAND THAT IS NOT CERTIFIED CLAIMED AS THE PROPERTY OF HEIRS - Mochammad Erwin Radityo (Jurnal Scientia, 2023)
Where’s the problem is that often the origin of the land inherited by the heir is unclear, especially if the heir does not have a valid legal basis as strong evidence of the inherited land. Often the heirs claim that the land is theirs because it is inherited from their parents as heirs, but cannot provide valid and strong evidence of ownership of the land. This paper discussed a formulation of the problem that will be the subject of discussion is: How is the validity of inheritance according to positive law in Indonesia, This research is normative juridical research, namely research that refers to legal norms contained in laws and regulations, court decisions and legal norms that exist in society. In this research, an analysis of a decision that has legal force will be carried out, namely Decision 53/Pdt.G/2018/PN Bnj. In this study, it can be concluded that if a land that is claimed does not have strong evidence, in this case the certificate as a basis for legal rights, then the person claiming it will not be comfortable owning and managing the land because there is no legal certainty or there is no legal standing over the ownership is that they do not have a Certificate of Ownership, even though the person has mastered it for a long time.